The Effect of Haematoporphyrin Derivative on the Uptake of 67Ga, 59Fe and 65Zn in Tumours - Phillips Carol, A.; Taylor, D.M. (Nuklearmedizin - NuclearMedicine, 1978)
The effect of prior administration of haematoporphyrin derivative on the uptake in tumours of 67Ga, 59Fe and 65Zn has been studied in tumour-bearing rats and mice. An approximately two-fold increase in the uptake of 67Ga was observed in the August 15 rat tumour when the nuclide was administered 17 to 24 hr after haematoporphyrin. No increase in the uptake of 67Ga occurred in three mouse tumours. Haematoporphyrin administration did not affect the uptake of 65Zn and 59Fe in any of the tumour systems. It is concluded that the presence of haematoporphyrin does not markedly increase the ability of tumours to accummulate metallic radionuclides.